Base material as well as preparation method and application thereof
By using base materials composed of zirconate and Group VIII metals, the problem of poor CO2 adsorption-catalytic cycle stability is solved, and the integrated integration of CO2 capture and conversion is achieved, energy consumption and cost are reduced, and transportation is avoided. Risk of leakage.
Patent Information
- Application Number
- CN202311039791.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-17
- Publication Date
- 2025-02-21
AI Technical Summary
In the existing CO2 capture and conversion technologies, the CO2 adsorption-catalytic cycle stability is poor, and the CO2 purification process has high energy consumption and cost, which poses a risk of transportation leakage.
The base material consisting of zirconate as CO2 adsorption component and Group VIII metals (such as Ni, Co, Fe) as catalytically active components is used to form efficient and stable CO2 adsorption-catalytic bifunctional materials through specific preparation methods. .
The integrated integration of CO2 capture and conversion is achieved, which improves the stability of CO2 adsorption-catalytic cycle, reduces energy consumption and costs, and avoids the risk of transportation leakage.
Smart Images

Figure CN119488873A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of carbon dioxide capture and conversion utilization, and in particular to a base material and a preparation method and application thereof. Background Art
[0002] Large-scale use of fossil fuels emits excessive CO into the atmosphere 2 , and has caused serious global warming and climate change problems, strengthening CO 2 Emission reduction work cannot be delayed. 2 Capture, utilization and storage (CCUS) is a new method to achieve the goal of reducing the CO 2 An important strategy for large-scale emission reduction.
[0003] Currently, CCUS technology faces CO 2 The capture and conversion processes are independent, CO 2 Conversion depends on high-purity CO 2 Gas source, CO 2 The purification process has high energy consumption and cost, and there are problems such as the risk of leakage during transportation. 2 Capture and convert on-site into value-added products to achieve CO 2 Integrated capture and conversion and process intensification are important approaches to solving the above problems.
[0004] Flue gas CO can be achieved based on adsorption-catalysis dual-functional materials 2 Capture and conversion are integrated. This strategy can directly utilize the waste heat of flue gas to achieve CO 2 Separation and conversion to produce synthetic fuels or value-added chemicals can avoid the cumbersome steps of material regeneration by temperature or pressure change in traditional carbon capture technology, greatly improving the overall efficiency and effectively avoiding CO 2 The risk of leakage during transportation and storage is of great environmental and economic significance.
[0005] CO 2 Adsorption-catalysis bifunctional materials are usually composed of alkali metal adsorption components and catalytic components. Catalytic components are usually divided into precious metal-based catalysts and transition metal-based catalysts. Although precious metal catalysts such as Ru and Rh have advantages such as good catalytic activity and strong stability, their practical application is limited by their high cost and low reserves. Transition metal catalysts such as Ni, Fe and Co have comparable catalytic activity to precious metal catalysts and have cost advantages. They have great potential in replacing precious metals to construct adsorption-catalysis bifunctional materials.
[0006] MgO and CaO are the basic components due to their abundance of raw materials, low cost and CO 2 It has the advantages of high adsorption capacity and has been reported to be used as a CO2 adsorption-catalytic bifunctional materials. 2 Adsorption performance usually depends on alkali metal molten salt doping. However, under medium and high temperature conditions, the decomposition loss of alkali metal molten salt and sintering of MgO can easily lead to CO 2 The adsorption and catalytic cycle activity decays. Calcium-based bifunctional materials are usually used in high-temperature CO 2 Capture and conversion, because the reaction temperature is higher than CaCO 3 The Tamman temperature is too high and the material is easily sintered and deactivated, resulting in a serious attenuation of its cyclic activity.
[0007] Therefore, an efficient and stable CO 2 Adsorption components, catalytic components and suitable synthesis methods to construct highly active CO 2 Adsorption-catalysis dual-functional materials. Summary of the invention
[0008] The purpose of the present invention is to overcome the CO 2 The problem of poor stability of the adsorption-catalysis cycle is solved, and a base material, a preparation method and application thereof are provided.
[0009] In order to achieve the above object, the present invention provides a base material in a first aspect, wherein the base material comprises a base CO 2 Adsorbed components and CO 2 Catalytically active components;
[0010] Wherein, the base CO 2 The adsorption component is selected from zirconate; the CO 2 The catalytically active component is selected from at least one of the Group VIII metals.
[0011] A second aspect of the present invention provides a method for preparing a base material, which comprises the following steps:
[0012] (1) dissolving a Group VIII metal salt, a Group I metal salt, a Zr salt and an additive in water respectively to form four solutions A, B, C and D;
[0013] (2) The four solutions A, B, C and D in step (1) are mixed to form a mixture, and the mixture is processed to obtain a base material.
[0014] The third aspect of the present invention provides a base material prepared by the method described in the second aspect of the present invention.
[0015] The fourth aspect of the present invention provides a use of the base material described in the first aspect and / or the third aspect of the present invention in carbon dioxide capture and in-situ conversion reactions.
[0016] Through the above technical solution, the beneficial effects of the present invention are as follows:
[0017] 1. The present invention provides a base adsorption-catalysis dual-functional material that can achieve CO 2 Capture and conversion are integrated. Compared with the basic bifunctional materials such as MgO and CaO reported in the literature, it has CO 2 The advantage of strong stability of adsorption-catalysis cycle.
[0018] 2. The preparation method of the base bifunctional material provided by the present invention is simple and feasible. By optimizing the active component precursor and regulating the ratio of the adsorption and catalytic active components, the microstructure, surface morphology, active component grain size, surface alkalinity and reduction properties of the base bifunctional material can be improved, so that the base bifunctional material has excellent adsorption and catalytic properties.
[0019] 3. The base bifunctional material provided by the present invention is suitable for CO with different partial pressures 2 Separation and conversion, can be applied to air source CO 2 Direct capture and conversion of stationary source flue gas CO in industries such as power, steel, chemical and cement 2 Capture and conversion, its application range is wide.
[0020] 4. The base bifunctional material provided by the present invention is applied to CO 2 During capture and in-situ conversion, there are a variety of reaction pathways to choose from. By selecting different reducing media and adjusting operating conditions, the reaction pathway and product distribution can be adjusted, which is more flexible in practical applications.
[0021] 5. The base bifunctional material provided by the present invention can utilize renewable energy to convert CO 2 Capturing and converting it in situ into value-added synthetic natural gas or syngas solves the problem of coordinated greenhouse gas emission reduction, realizes the recycling of C1 resources and efficient storage of clean energy, and has great economic value and environmental significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The Ni@Na prepared in Example 1 of the present invention 2 ZrO 3 Scanning electron microscopy image of the base bifunctional material;
[0023] Figure 2 The Ni@Na prepared in Example 1 of the present invention 2 ZrO 3 X-ray diffraction pattern of base bifunctional materials;
[0024] Figure 3 The Ni@Na prepared in Example 1 of the present invention 2 ZrO 3CO of base bifunctional materials 2 Temperature programmed desorption curve;
[0025] Figure 4 The Ni@Na prepared in Example 1 of the present invention 2 ZrO 3 H of base bifunctional materials 2 Programmed temperature reduction curve;
[0026] Figure 5 The Ni@Na prepared in Example 1 of the present invention 2 ZrO 3 CO of base bifunctional materials 2 Gas concentration evolution curve of adsorption-catalysis process;
[0027] Figure 6 The Ni@Na prepared in Example 1 of the present invention 2 ZrO 3 CO of the Ni@CaO base bifunctional material and the Ni@CaO base bifunctional material provided in Comparative Example 1 2 Adsorption-catalysis cycle stability. (a) Ni@Na 2 ZrO 3 Base bifunctional materials; (b) Ni@CaO base bifunctional materials. DETAILED DESCRIPTION
[0028] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0029] The first aspect of the present invention provides a base material, wherein the base material comprises a base CO 2 Adsorbed components and CO 2 Catalytically active components;
[0030] Wherein, the base CO 2 The adsorption component is selected from zirconate; the CO 2 The catalytically active component is selected from at least one of the Group VIII metals.
[0031] In some embodiments of the present invention, preferably, the base CO 2 The adsorbent component is selected from Li 2 ZrO 3 、Na 2 ZrO 3 and K 2 ZrO 3 At least one of the CO 2 The catalytically active component is selected from at least one of Ni, Co and Fe.
[0032] In the present invention, the load may be the CO 2 The catalytic components are distributed in the base CO in the form of surface support and bulk embedding. 2 adsorbed components.
[0033] In some embodiments of the present invention, preferably, based on the total mass of the base material, the CO 2 The mass fraction of the catalytically active component is 5-20%. 2 When the mass fraction of the catalytically active component is less than the above range, it will lead to insufficient surface basic site density of the base material and CO 2 The technical effect of poor adsorption performance is that when the CO 2 The mass fraction of catalytically active components greater than the above range will lead to the accumulation and uneven distribution of base adsorption components, covering the catalytic active sites and CO 2 The technical effect of reducing adsorption and catalytic performance. Preferably, the base CO 2 The mass fraction of the adsorbed component is 80-95%.
[0034] In the present invention, when the CO 2 When the mass fraction of the catalytically active components is within the range of 5-20%, the surface active components of the base material are evenly distributed, the surface basicity is high, the reduction activity is strong, and most of the catalytically active components are highly dispersed in the base CO in a supported form. 2 Surfaces on which components are adsorbed.
[0035] In some embodiments of the present invention, preferably, the yield decay rate of the base material after 10 cycles is less than 10%.
[0036] A second aspect of the present invention provides a method for preparing a base material, which comprises the following steps:
[0037] (1) dissolving a Group VIII metal salt, a Group I metal salt, a Zr salt and an additive in water respectively to form four solutions A, B, C and D;
[0038] (2) The four solutions A, B, C and D in step (1) are mixed to form a mixture, and the mixture is processed to obtain a base material.
[0039] In some embodiments of the present invention, preferably, the Group VIII metal salt is at least one selected from the group consisting of acetates or nitrates of Ni, Co and Fe.
[0040] In some embodiments of the present invention, preferably, the Group I metal salt is selected from at least one of acetates or nitrates of Li, Na and K.
[0041] In some embodiments of the present invention, preferably, the Zr salt is zirconyl nitrate or zirconium oxychloride.
[0042] In some embodiments of the present invention, preferably, the auxiliary agent is oxalic acid or citric acid.
[0043] In some embodiments of the present invention, preferably, in step (1), the concentration of the Group VIII metal salt in the solution A is 0.1-0.5 mol / L; when the concentration of the Group VIII metal salt is less than the range, it will lead to the technical effect of limited loading of the catalytic component on the surface of the base adsorption component and poor catalytic activity; when the concentration of the Group VIII metal salt is greater than the range, it will lead to the technical effect of aggregation of the catalytic component and uneven distribution on the surface of the base adsorption component and attenuation of the catalytic activity.
[0044] In some embodiments of the present invention, preferably, in step (1), the concentration of the Group I metal salt in the solution B is 0.1-0.5 mol / L; when the concentration of the Group I metal salt is less than the above range, the alkaline active site density is limited and CO 2 The technical effect of poor adsorption performance is that when the concentration of the Group I metal salt is greater than the above range, it will lead to uneven distribution of alkaline active sites and CO 2 Technical effect of adsorption performance decay.
[0045] In some embodiments of the present invention, preferably, in step (1), the concentration of the Zr salt in the solution C is 0.05-0.25 mol / L; when the concentration of the Zr salt is less than the above range, the complexation rate of the Zr salt with the Group I metal salt is slow, the content of the basic zirconate adsorption component is limited and CO 2 The technical effect of poor adsorption performance is that when the concentration of the Zr salt is greater than the above range, the Zr salt will be complexed with the metal salt of the first main group to form a base zirconate adsorption component with uneven distribution and CO 2 Technical effect of reduced adsorption performance.
[0046] In some embodiments of the present invention, preferably, in step (1), the concentration of the auxiliary agent in the solution D is 0.1-0.5 mol / L; when the concentration of the auxiliary agent is less than the range, it will lead to insufficient complexation of the Zr salt with the Group I metal salt and the Group VIII metal salt and limited content of the adsorption and catalytic components; when the concentration of the auxiliary agent is greater than the range, it will lead to too fast complexation rate of the adsorption and catalytic components, aggregation of components and uneven distribution of active sites.
[0047] In some embodiments of the present invention, preferably, the molar ratio of the Group I metal salt to the Zr salt is 3:1-1:1, more preferably 2:1; when the molar ratio of the Group I metal salt to the Zr salt is less than the range, it will lead to the technical effects of low density of alkaline adsorption sites and coverage of active sites, and when the molar ratio of the Group I metal salt to the Zr salt is greater than the range, it will lead to the technical effects of aggregation of base adsorption components and uneven distribution of alkaline sites.
[0048] In some embodiments of the present invention, preferably, the molar ratio of the auxiliary agent to the metal element in the Group VIII metal salt is 2: 1-1: 2, more preferably 1: 1. When the molar ratio of the auxiliary agent to the metal element in the Group VIII metal salt is less than the above range, the adsorption and catalytic components cannot be fully complexed and the adsorption and catalytic components are limited in content. When the molar ratio of the auxiliary agent to the metal element in the Group VIII metal salt is greater than the above range, the adsorption and catalytic components are aggregated and unevenly distributed.
[0049] In some embodiments of the present invention, preferably, the dissolution temperature in step (1) is 20-50°C; the dissolution time is 1-2h; when the dissolution temperature is less than the range, the metal salts of Group VIII, Group I, Zr salts and additives cannot be fully dissolved, resulting in a technical effect of limited active component content; when the dissolution temperature is greater than the range, the metal salts of Group VIII, Group I, Zr salts and additives are concentrated and the concentration deviates from the preferred range; when the dissolution time is less than the range, the metal salts of Group VIII, Group I, Zr salts and additives cannot be fully dissolved, resulting in a technical effect of limited active component content; when the dissolution time is greater than the range, the metal salts of Group VIII, Group I, Zr salts and additives are concentrated and the concentration deviates from the preferred range.
[0050] In some embodiments of the present invention, preferably, in step (2), the mixing temperature is 120-200°C; the mixing stirring speed is 100-300rpm; the mixing time is 4-8h; when the mixing temperature is less than the range, it will lead to the technical effect of slow complexation reaction rate of Zr salt with Group I metal salt and Group VIII metal salt and insufficient complexation; when the mixing temperature is greater than the range, it will lead to the technical effect of auxiliary agent decomposition loss and incomplete complexation; when the mixing time is less than the range, it will lead to the technical effect; when the mixing time is greater than the range, it will lead to the technical effect of insufficient complexation of Zr salt with Group I metal salt and Group VIII metal salt; when the mixing stirring speed is less than the range, it will lead to the technical effect of uneven dispersion and insufficient complexation of Group VIII metal salt, Group I metal salt and Zr salt during the complexation process; when the mixing stirring speed is greater than the range, it will lead to the technical effect that Group VIII metal salt, Group I metal salt and Zr salt cannot form a stable complex system.
[0051] In some embodiments of the present invention, preferably, the processing comprises: evaporating the water in the mixture, then calcining, and finally pre-reducing.
[0052] In the present invention, the reduction can be completed when the base material is prepared, or the risk of oxidation during storage and transportation of the material can be considered, and the material can be reduced in situ when it is used for reaction. 2 Pre-reduction treatment in adsorption-catalytic applications.
[0053] The third aspect of the present invention provides a base material prepared by the method described in the second aspect of the present invention.
[0054] The fourth aspect of the present invention provides a use of the base material described in the first aspect and / or the third aspect of the present invention in carbon dioxide capture and in-situ conversion reactions.
[0055] In some embodiments of the present invention, preferably, the carbon dioxide capture and in-situ conversion reaction includes: carbon dioxide adsorption and in-situ methanation, in-situ reverse water gas shift and in-situ methane reforming, and production of natural gas or synthesis gas.
[0056] In the present invention, the room temperature refers to 25±5°C.
[0057] The present invention will be described in detail below through examples. 2 The adsorption capacity and product yield parameters are calculated by integrating the gas concentration; the test instruments, fixed bed reactor and infrared flue gas analyzer, are commercially available products from Nanjing Haoerpu Analytical Equipment Co., Ltd. and MRU of Germany, respectively.
[0058] Example 1
[0059] Ni@Na 2 ZrO 3 Preparation of base bifunctional materials: According to the NiO loading of 10wt%, 1.67g of Ni(CH 3 COO 2 ·4H 2 O was dissolved in 27 mL of deionized water and stirred in a water bath at room temperature for 30 min to form a uniform nickel acetate solution (solution A). 3 COONa·3H 2 O was dissolved in 100 mL of deionized water and stirred in a water bath at room temperature for 30 min to form a uniform sodium acetate solution (solution B). According to the molar ratio of Na to Zr of 2:1, 7.95 g of Zr (CH 3 COO 4 Dissolve in 100 mL of deionized water and stir in a water bath at room temperature for 30 min to form a uniform zirconium acetate solution (solution C). According to the molar ratio of the additive to the three metals Na, Zr and Ni being 1:1, weigh 16.73 g of C 6 H 8 O 7 ·H 2 O was dissolved in 160 mL of deionized water and stirred in a water bath at room temperature for 30 min to form a uniform citric acid solution (solution D).
[0060] The above precursor salt solutions were mixed, and stirred in a water bath at room temperature for 30 minutes to form a uniform mixture. The citric acid solution was added dropwise to the above precursor salt mixture, and stirred in a water bath at room temperature for 30 minutes to form a uniform mixture.
[0061] The mixture was processed by placing it in an oil bath and stirring it for 6 hours at an oil bath temperature of 150°C at a stirring speed of 200 rpm until the water evaporated. The obtained powder mixture was placed in a muffle furnace and calcined at 800°C for 4 hours in an air atmosphere to obtain Ni@Na 2 ZrO 3 Base bifunctional materials.
[0062] Ni@Na 2 ZrO 3 CO of base bifunctional materials 2 Adsorption-catalytic performance test: Weigh 0.1g of Ni@Na 2 ZrO 3 The base bifunctional material is placed in a fixed bed reactor and 2 The temperature was raised to 650°C at a rate of 10°C / min under a nitrogen atmosphere, and then 100% H 2The base bifunctional material was reduced for 2 h. The gas was then switched to pure N 2 Purge for 5 minutes, wait until the fixed bed outlet position H 2 The concentration dropped to 0 and 10% CO was introduced 2 / N 2 Maintain CO for 25 min 2 Adsorption test. Then, pure N was introduced into the reactor. 2 Purge for 10 minutes, and wait for CO to form at the fixed bed outlet. 2 The concentration dropped to 0 and the gas was switched to 35% H 2 The in-situ catalytic experiment was carried out for 30 min. After the reaction was completed, N 2 Purge and repeat the above CO 2 Adsorption and in situ catalytic experiments to evaluate Ni@Na 2 ZrO 3 The cyclic stability of the base bifunctional material is shown in Table 1.
[0063] Example 2
[0064] Co@Na 2 ZrO 3 Preparation of base bifunctional materials: According to the CoO loading of 10wt%, 1.66g of Co(CH 3 COO 2 ·4H 2 O was dissolved in 27 mL of deionized water and stirred in a water bath at room temperature for 30 min to form a uniform cobalt acetate solution (solution A). 3 COONa was dissolved in 100 mL of deionized water and stirred in a water bath at room temperature for 30 min to form a uniform sodium acetate solution (solution B). 7.95 g of Zr (CH 3 COO 4 Dissolve in 100 mL of deionized water and stir in a water bath at room temperature for 30 min to form a uniform zirconium acetate solution (Solution C). Mix the above precursor salt solutions and stir in a water bath at room temperature for 30 min to form a uniform mixed solution. According to the molar ratio of the additive to Na, Zr and Co metals of 1:1, weigh 16.73 g of C 6 H 8 O 7 ·H 2 O was dissolved in 160 mL of deionized water and stirred in a water bath at room temperature for 30 min to form a uniform citric acid solution (solution D).
[0065] The citric acid solution was added dropwise to the precursor salt mixture, and stirred in a water bath at room temperature for 30 minutes to form a uniform mixture.
[0066] The mixture was processed by placing it in an oil bath and stirring it for 6 hours at an oil bath temperature of 150°C at a stirring speed of 200 rpm until the water evaporated. The obtained powder mixture was placed in a muffle furnace and calcined at 800°C for 4 hours in an air atmosphere to obtain Co@Na 2 ZrO 3 Base bifunctional materials.
[0067] Co@Na 2 ZrO 3 CO of base bifunctional materials 2 Adsorption-catalytic performance test: The specific process is the same as that in Example 1. Co@Na 2 ZrO 3 The cyclic stability results of the base bifunctional materials are shown in Table 1.
[0068] Example 3
[0069] Ni@Li 2 ZrO 3 Preparation of base bifunctional materials: According to the NiO loading of 10wt%, 1.67g of Ni(CH 3 COO 2 ·4H 2 O was dissolved in 67 mL of deionized water and stirred in a water bath at room temperature for 30 min to form a uniform nickel acetate solution (solution A). 3 COOLi·2H 2 O was dissolved in 118 mL of deionized water and stirred in a water bath at room temperature for 30 min to form a uniform lithium acetate solution (solution B). According to the molar ratio of Li to Zr of 2:1, 9.61 g of Zr (CH 3 COO 4 Dissolve in 116 mL of deionized water and stir in a water bath at room temperature for 30 min to form a uniform zirconium acetate solution (solution C). According to the molar ratio of the additive to Li, Zr and Ni metals of 1:1, weigh 19.92 g of C 6 H 8 O 7 ·H 2 O was dissolved in 190 mL of deionized water and stirred in a water bath at room temperature for 30 min to form a uniform citric acid solution (solution D).
[0070] The above precursor salt solutions were mixed, and stirred in a water bath at room temperature for 30 minutes to form a uniform mixture. The citric acid solution was added dropwise to the above precursor salt mixture, and stirred in a water bath at room temperature for 30 minutes to form a uniform mixture.
[0071] The mixture was processed by placing it in an oil bath pot and stirring it continuously for 6 hours at an oil bath temperature of 150°C at a stirring speed of 200 rpm until the water evaporated. The obtained powder mixture was placed in a muffle furnace and calcined at 800°C for 4 hours in an air atmosphere to obtain Ni@Li 2 ZrO 3 Base bifunctional materials.
[0072] Ni@Li 2 ZrO 3 CO of base bifunctional materials 2 Adsorption-catalytic performance test: The specific process is consistent with Example 1. Ni@Li 2 ZrO 3 The cyclic stability results of the base bifunctional materials are shown in Table 1.
[0073] Example 4
[0074] Using the Ni@Na obtained in Example 1 2 ZrO 3 CO of base bifunctional materials 2 Adsorption-catalytic performance test, the difference is that the concentration of hydrogen in the in-situ catalytic experiment is replaced by "65%" instead of "35%". The details are as follows: weigh 0.1g Ni@Na 2 ZrO 3 The base bifunctional material is placed in a fixed bed reactor and 2 The temperature was raised to 650°C at a rate of 10°C / min under a nitrogen atmosphere, and then 100% H 2 The base bifunctional material was reduced for 2 h. The gas was then switched to pure N 2 Purge for 5 minutes, wait until the fixed bed outlet position H 2 The concentration dropped to 0 and 10% CO was introduced 2 / N 2 Maintain CO for 25 min 2 Adsorption test. Then, pure N was introduced into the reactor. 2 Purge for 10 minutes, and wait for CO to form at the fixed bed outlet. 2 The concentration dropped to 0 and the gas was switched to 65% H 2 The in-situ catalytic experiment was carried out for 30 min. After the reaction was completed, N 2 Purge and repeat the above CO 2 Adsorption and in situ catalytic experiments to evaluate Ni@Na 2 ZrO 3 The cyclic stability of the base bifunctional material is shown in Table 1.
[0075] Comparative Example 1
[0076] Preparation of Ni@CaO base bifunctional material: Weigh 14.16 g of Ca(CH 3 COO 2 ·H 2 O was dissolved in 160 mL of deionized water and stirred in a water bath at room temperature for 30 min to form a uniform calcium acetate solution. According to the NiO loading of 10 wt.%, 1.67 g of Ni(CH 3 COO 2 ·4H 2 O was dissolved in 67 mL of deionized water and stirred in a water bath at room temperature for 30 min to form a uniform nickel acetate solution. The above precursor salt solutions were mixed and stirred in a water bath at room temperature for 30 min to form a uniform mixed solution. According to the molar ratio of the additive to Ca and Ni metal being 1:1, 18.28 g of C 6 H 8 O 7 ·H 2 O was dissolved in 174 mL of deionized water and stirred in a water bath at room temperature for 30 min to form a uniform citric acid solution. The citric acid solution was added dropwise to the above-mentioned precursor salt mixture and stirred in a water bath at room temperature for 30 min to form a uniform mixed liquid system. The mixed system was placed in an oil bath pot and stirred continuously at an oil bath temperature of 150 ° C until the water evaporated. The obtained powder mixture was placed in a muffle furnace and calcined at 800 ° C for 4 h in an air atmosphere to obtain the Ni@CaO base bifunctional material.
[0077] Ni@CaO-based bifunctional CO materials 2 Adsorption-catalytic performance test: The specific process is consistent with Example 1. The cyclic stability results of the Ni@CaO base bifunctional material are shown in Table 1.
[0079] Comparative Example 2
[0080] Preparation of Co@CaO base bifunctional material: Weigh 14.16 g of Ca(CH 3 COO 2 ·H 2 O was dissolved in 160 mL of deionized water and stirred in a water bath at room temperature for 30 min to form a uniform calcium acetate solution. According to the CoO loading of 10 wt%, 1.66 g of Co(CH 3 COO 2 ·4H 2 O was dissolved in 67 mL of deionized water and stirred in a water bath at room temperature for 30 min to form a uniform cobalt acetate solution. The above precursor salt solutions were mixed and stirred in a water bath at room temperature for 30 min to form a uniform mixed solution. According to the molar ratio of the additive to Ca and Co metals of 1:1, 18.28 g of C 6 H 8 O 7·H 2 O was dissolved in 174 mL of deionized water and stirred in a water bath at room temperature for 30 min to form a uniform citric acid solution. The citric acid solution was added dropwise to the above-mentioned precursor salt mixture and stirred in a water bath at room temperature for 30 min to form a uniform mixed liquid system. The mixed system was placed in an oil bath pot and stirred continuously at an oil bath temperature of 150 ° C until the water evaporated. The obtained powder mixture was placed in a muffle furnace and calcined at 800 ° C for 4 h in an air atmosphere to obtain the Co@CaO base bifunctional material.
[0081] CO@CaO-based bifunctional materials 2 Adsorption-catalytic performance test: The specific process is consistent with Example 1. The cyclic stability results of the Co@CaO base bifunctional material are shown in Table 1.
[0082] Table 1 CO of base bifunctional materials corresponding to different embodiments 2 Comparison of adsorption-catalysis cycle stability
[0083]
[0084]
[0085] It can be seen from the results in Table 1 that the base materials prepared by Examples 1-3 of the technical solution of the present invention can capture carbon dioxide and react with in-situ reverse water gas shift reaction. 2 The cyclic attenuation rate of adsorption capacity and the cyclic attenuation rate of product yield are lower than those of Comparative Examples 1 and 2, indicating that the base material prepared by the technical scheme of the present invention has a high adsorption capacity in CO 2 It has significantly better technical effects in terms of adsorption-catalysis cycle stability.
[0086] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A base material, wherein: The base material includes a base CO2 adsorption component and a CO2 catalytic active component supported on the base CO2 adsorption component; Wherein, the basic CO2 adsorption component is selected from zirconate; and the CO2 catalytic active component is selected from at least one of the Group VIII metals.
2. The base material according to claim 1, wherein The basic CO2 adsorption component is selected from at least one of Li2ZrO3, Na2ZrO3 and K2ZrO3; the CO2 catalytic active component is selected from at least one of Ni, Co and Fe.
3. The base material according to claim 1 or 2, wherein Based on the total mass of the base material, the mass fraction of the CO2 catalytic active component is 5-20%.
4. A method for preparing a base material, characterized in that: The following steps are involved: (1) dissolving a Group VIII metal salt, a Group I metal salt, a Zr salt and an additive in water respectively to form four solutions A, B, C and D; (2) The four solutions A, B, C and D in step (1) are mixed to form a mixture, and the mixture is processed to obtain a base material.
5. The method according to claim 4, wherein: The Group VIII metal salt is selected from at least one of the acetates or nitrates of Ni, Co and Fe; And / or, the Group I metal salt is at least one selected from acetates or nitrates of Li, Na and K; And / or, the Zr salt is zirconium oxynitrate or zirconium oxychloride; And / or, the auxiliary agent is oxalic acid or citric acid.
6. The method according to claim 4 or 5, wherein: In step (1), the concentration of the Group VIII metal salt in the solution A is 0.1-0.5 mol / L; And / or, in step (1), the concentration of the Group I metal salt in the solution B is 0.1-0.5 mol / L; And / or, in step (1), the concentration of the Zr salt in the solution C is 0.05-0.25 mol / L; And / or, in step (1), the concentration of the auxiliary agent in the solution D is 0.1-0.5 mol / L; And / or, the molar ratio of the Group I metal salt to the Zr salt is 3:1-1:1; And / or, the molar ratio of the auxiliary agent to the metal element in the Group VIII metal salt is 2:1-1:
2.
7. The method according to any one of claims 4 to 6, wherein: The dissolution temperature in step (1) is 20-50° C. and the dissolution time is 1-2 h. And / or, in step (2), the mixing temperature is 120-200°C; the mixing stirring speed is 100-300 rpm; the mixing time is 4-8h; And / or, the processing process includes: evaporating the water in the mixture, then calcining, and finally reducing.
8. A base material obtained by the method according to any one of claims 4 to 7.
9. Use of the base material according to any one of claims 1 to 3 and 8 in carbon dioxide capture and in-situ conversion reactions.
10. The use according to claim 9, wherein: The in-situ conversion reaction is at least one of an in-situ methanation reaction, an in-situ reverse water gas shift reaction and an in-situ methane reforming reaction.
Citation Information
Patent Citations
Method for preparing carbon dioxide adsorbent ceramic by template method
CN106747607A
Method for preparing zirconia loaded sulfur-resistant methane catalyst
CN108479754A
Ni / CaO bifunctional catalyst modified by MgO and preparation method and application of Ni / CaO catalyst
CN110433811A
Carbon dioxide adsorption-desorption material and adsorption-desorption apparatus
CN1784268A
Alkali Metal-Based Solid Sorbent for Carbon Dioxide Capture with Low Temperature Regeneration
KR1020090033300A